ANALYSIS OF FINANCIAL REPORT PERFORMANCE AS A DETERMINANT OF COOPERATIVE PERFORMANCE BASED ON THE BALANCED SCORECARD METHOD: Case Study of the Prosperous Cooperative of SMA NEGERI 3 SUBANG - Dede Entis; Elsa Auliya Agustien; Trisandi Eka Putri (JABI (Journal of Accounting and Business Issues), 2023)
Cooperatives play a strategic role in promoting fair and equitable development that results in advancing members and the wider community, supporting the realization of national development, and improving the standard of living of the community. Therefore, cooperatives must maintain trust in the financial management of their members and the community. A sign of the cooperative's seriousness in managing community membership and funding is maintaining a healthy business continuity, because performance is very important for the business. The survey method used is a descriptive survey. “Descriptive research is research about a particular phenomenon or group obtained by a researcher or subject from many people, organizations, industries, or other perspectives.” In addition, descriptive research is research conducted to determine the value of one or more independent variables without making comparisons or connecting with other variables. Identifying the performance progress, health status, and assessment process related to the implementation of the prosperous cooperative activities of SMAN 3 Subang in the financial sector between 2020 and 2021. The perspectives used are the financial perspective, internal business, learning and growth, and the customer perspective. Describe your success in carrying out cooperative activities and achieving the goals that have been set. The goals set will be the basis for measuring the cooperative's performance. From the results of the Financial Statements of the Prosperous Cooperative of SMAN 3 Subang on the total score of the Balanced Scorecard and four perspectives in 2021, an average score of 36 and a total weight of 100 were obtained. This cooperative has set goals that have not been achieved. Therefore, the cooperative needs to make some improvements both from a financial perspective and from a customer perspective in order to further improve both perspectives in the future.